A promising chemical series of positive allosteric modulators of the μ-opioid receptor that enhance the antinociceptive efficacy of opioids but not their adverse effects. (1st September 2021) - Pryce, Kerri D.; Kang, Hye Jin; Sakloth, Farhana; Liu, Yongfeng; Khan, Susan; Toth, Katalin; Kapoor, Abhijeet; Nicolais, Andrew; Che, Tao; Qin, Lihuai; Bertherat, Feodora; Kaniskan, H. Ümit; et al.
Abstract: Positive allosteric modulators (PAMs) of the μ-opioid receptor (MOR) have been proposed to exhibit therapeutic potential by maximizing the analgesic properties of clinically used opioid drugs while limiting their adverse effects or risk of overdose as a result of using lower drug doses. We herein report in vitro and in vivo characterization of two small molecules from a chemical series of MOR PAMs that exhibit: (i) MOR PAM activity and receptor subtype selectivity in vitro, (ii) a differential potentiation of the antinociceptive effect of oxycodone, morphine, and methadone in mouse models of pain that roughly correlates with in vitro activity, and (iii) a lack of potentiation of adverse effects associated with opioid administration, such as somatic withdrawal, respiratory depression, and analgesic tolerance. This series of MOR PAMs holds promise for the development of adjuncts to opioid therapy to mitigate against overdose and opioid use disorders. Highlights: MOR PAMs hold promise for the development of adjuncts to opioid therapy. MOR PAM activity does not appear to require biased signaling. Differential enhancement of the antinociceptive effect of classical opioid drugs. Lack of potentiation of tolerance, withdrawal, and respiratory depression.